Surgical treatment of lateral and posterior process fractures of the talus: Mid-term results of 15 cases after 7 years. Issue 1 (January 2020) - von Winning, Dominik; Lippisch, Roland; Pliske, Gerald; Adolf, Daniela; Walcher, Felix; Piatek, Stefan
Highlights: 15 cases with surgery of talar process fractures with a mean follow-up of 7 years. Good clinical outcomes after screw compression internal fixation. Delayed surgery did not lead to poorer outcomes in our patients. Abstract: Background: We retrospectively evaluated the mid-term results of surgery for talar process fractures (lateral and posterior processes) and exploratively analyzed parameters that potentially impact treatment outcomes. Methods: Fifteen patients who underwent internal fixation (January 2000 to December 2015) were examined for radiological and clinical functional outcomes. The independent parameters evaluated were age, sex, extent of general injury, soft-tissue damage, surgical latency, and fracture type. Results: All fractures healed completely. Three patients developed osteoarthritis. The American Orthopaedic Foot and Ankle Society Ankle/Hindfoot Scale score was 79.5 ± 18.6, the Functional Foot Index score was 31.1 ± 31.4, and the physical and mental component summary scores of the Short Form 36, version 2, were 46.6 ± 11.8 and 50.3 ± 9.1, respectively. No influence on the above scores was determined. Conclusions: The clinical outcomes of internal fixation of talar process fractures were good. Delayed surgical treatment (≥14 days) did not significantly lead to poorer outcomes in our patients.